Pengaruh Model Pembelajaran Kooperatif Tipe Group Investigation (GI) Terhadap Kemampuan Berpikir Kritis Siswa Kelas X Pada Materi Ekosistem - Putri, Izharina Tania; Amirullah, Gufron; Suciatia, Rizkia; Susilo, Susilo (IAIN Ternate, 2023)
The research was aimed to know the effect model of cooperative learning type group investigation (GI) toward critical thinking ability of students grade X on the material ecosystems at Senior High School 66 South Jakarta. The research was conducted in March 24 until May 20, 2016. The method used Quasi Eksperimental, design Pretest – Posttest Contol Group Design. The population in this study were all students of class X MIA (total 108 siswa), through sampling by using Cluster Random Sampling. The instrument used essay test as much as 10 question integrated with six indicator critical thinking ability (formulate problems, argues, make deductions, induction, evaluating, and take decisions and actions). The result showed that N-gain average critical thinking ability in experiment class was ( = 32,36) it was higher than control class ( = 18,97). The hypotesis test with t test (sig 1%) eamed value thit (7,08) and ttable (2,38), because thit >ttable then H0 rejected. Therefore, it can be concluded that the effect model of cooperative learning type Group Investigation (GI) toward critical thinking ability of students grade X on the material ecosystems in Senior High School 66 South Jakarta.Keyword : Group Investigation model, critical thinking ability, ecosystem material